Development of Interpersonal Learning Models in Islamic Religious - Ajamalus; Nur Ainiyah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The purpose of this study is to develop a learning model to improve interpersonal skills in Islamic religious education subjects that are feasible and practical. This research is R&D research. The data was obtained by expert judgment on the prototype model developed, observations on the applicability of the learning model developed, and Student responses during field trials. The subjects of this study were junior high school students in Indonesia with a sample of 116, which was determined by a simple random sampling technique. This study obtains a learning model to improve interpersonal skills that are feasible and practical, as evidenced by 1) the average number of expert validations is 3.76 or in the very high category, 2) the assessment of the applicability of the model in the field is 0.8 or in the very good category, and 3) the average score of student responses to the application of this model is 0.8 or in the very good category.